Pengaruh Suplementasi Zat Besi yang Dikombinasikan dengan Jus Lemon terhadap Pencegahan Anemia pada Remaja Putri: The Effect of Iron Supplementation Combined with Lemon Juice on Anemia Prevention among Adolescent Girls - Arnita, Beny (Chakra Brahmanda Lentera Institute, 2026)
Adolescent girls are at high risk of iron deficiency anemia due to increased iron requirements during growth and menstrual blood loss. Although iron supplementation tablets are widely used for anemia prevention, iron absorption remains suboptimal. Lemon juice, a natural source of vitamin C, may enhance iron absorption and improve hemoglobin levels. This pre-experimental study used a one-group pretest–posttest design involving 47 adolescent girls in Bandar Surabaya Village, Central Lampung, Indonesia. Participants received iron supplementation tablets combined with lemon juice for four weeks. Hemoglobin levels were measured before and after the intervention using a portable hemoglobin analyzer. Data were analyzed using a paired t-test with a significance level of p < 0.05. Mean hemoglobin levels increased from 14.72 g/dL before the intervention to 15.80 g/dL after the intervention. The proportion of participants with hemoglobin levels <12 g/dL decreased from 4.3% to 0%. Statistical analysis showed a significant improvement in hemoglobin levels following the intervention (p = 0.001). Iron supplementation combined with lemon juice effectively improved hemoglobin levels among adolescent girls. This combination may serve as a simple and affordable complementary strategy to strengthen anemia prevention programs.